Comparative analysis of antioxidative potentials of extracts of defatted unfermented and fermented locust beans (Bangladesh Journal of Scientific and Industrial Research, 2015)
Preliminary investigation on antioxidative potentials of defatted fermented locust bean extract in comparison to defatted non-fermented locust bean was conducted. Qualitative antioxidative assessment on the extract was accomplished by screening the phytochemical endowment, and similar bioactive components. Also some antioxidative indices: relative reducing power (mg ascorbic acid reducing activity equivalent per mg sample), radical scavenging activity(%) and free amino acids (mg glycine activity equivalent per mg sample), were quantitatively evaluated. Phytochemical screening results showed that the defatted fermented samples were characterized with high strength presence of bioactive compounds notably phenolic compounds, saponins, peptides, amino acid and reductones. However, alkaloids and flavonoids were not detected. UV-Spectral characteristics of the extracts corroborated same. Similarly, quantitative antioxidative markers evaluated showed that the antioxidative capacity in terms of relative reducing power (23.40-29.50), and radical scavenging activity (82-89) on 1,1-diphenyl-2-picrylhydrazyl (DPPH) of defatted fermented locust bean extracts were high in comparison to the low antioxidative capacity in terms of relative reducing power 10.00-13.30) and radical scavenging activity (53-57) of the corresponding defatted unfermented locust bean extract. In addition the free amino acid of the defatted fermented locust bean extracts were high (1.66-3.30) in comparison to the low (0.215-0.3) free amino acid of the defatted unfermented locust bean extract. The result of total phenolic content was variable. Also, the antioxidant activity rate content, and EC50 of the extract were evaluated. This study demonstrated high antioxidant endowment of fermented locust beans in comparison to non-fermented locust beans. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22632 Bangladesh J. Sci. Ind. Res. 49(4), 275-280, 2014